Randomized clinical trial evaluating the effect of splinting crowns on short implants in the mandible 3 years after loading. Issue 11 (12th September 2020) - Al‐Sawaf, Omar; Tuna, Taskin; Rittich, Anne; Kern, Thomas; Wolfart, Stefan
Abstract: Objective: To compare the radiographic marginal bone loss and clinical parameters of splinted and non‐splinted fixed dental prostheses on short implants in the posterior region of the lower jaw 3 years after loading. Material and Methods: Twenty patients, 15 female and five males, with uni‐ or bilateral free‐end situations in the mandible participated in the study. Two short implants (7 mm) in the posterior mandible were placed and patients were randomized to receive splinted ( n  = 11) or non‐splinted ( n  = 13) cemented crowns. Marginal bone loss (MBL) was assessed on radiographs taken with customized positioning jigs at baseline, 1 and 3 years after loading. Plaque index (PI), gingival index (GI), probing depth (PD), and bleeding on probing (BOP) were measured. (ClinicalTrials.gov; identifier: NCT03558347). Results: After 3‐year survival rate of altogether 48 implants was 100% for both groups. Success rate (according to Papaspyridakos, Chen, Singh, Weber, & Gallucci, 2012) was 84.6% for non‐splinted and 86.4% for splinted implants. At restoration level survival rate was 100% for both groups. Marginal bone level changes showed mean gain of 0.3 ± 0.8 mm for non‐splinted and 0.1 ± 0.5 mm for splinted implants 3 years after loading. Statistical analysis showed no significant difference in PI, GI, PD, BOP, and marginal bone loss between both groups ( p  > .05). Conclusion: Within the limitations of this study it can be concluded that splinting crowns on short implants neither seems to affect the amount of marginal bone loss nor peri‐implant health 3 years after loading.